Comparison of Corrosion Rate on Paint Coated and Uncoated SS400 Steel - Eko Hariyadi; Mohammad Jufri; Hasanuddin Hasanuddin (University of Muhammadiyah Malang, 2017)
To prevent corrosion in metal, especially carbon steel, always need efforts which considered expensive one. But, compared with costs and losts when the corrosion attack is not properly managed then the cost of efforts is much lower. The most popular method in preventing corrosion attack is by coating of metal which also has decorative objective. In this research, four coating materials were applied to the surface of low carbon steel strips (SS400) and as control uncoated SS400 steel strips were also employed. The steel strips then were dipped into electrolite solution consisted of 30% of consentration of H2SO4, and NaCl soluted in river water for 15 (fifteen) days. After the presetted time was elapsed, the steel strips then examined for lost of mass. It was found that the highest lost of mass was for unpolished uncoated one dipped in H2SO4 with corrosion rate of 4,566.06 mpy. The lowest lost was for paint coated one dipped in NaCl-river water solution with corroion rate of 0.64 mpy.